A New Multilevel Active Power Filter Using Switches Meticulously Controlled - Zoubir Zahzouh; Lakhdar Khochmane; Ali Haddouche (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Shunt active power filter based on multilevel inverter is used to compensate the power factor and to delete the harmonics. This one permits to reduce the inverse voltages applied to the filter switches and their switching frequencies. Nevertheless, the high number of used switches requires a complicated controller and increases the switching losses; where the necessity of finding another resolution system. In this work a new topology of multilevel inverter is proposed as a shunt active power filter using two IGBT transistors in series of opposite sense meticulously controlled by a parallel control algorithm, with the concept of reduced number of six switches which are able to create five levels of the output voltage. This system substute the classical system of eight switches. The harmonic currents identification is carried out using the instantaneous active and reactive power method. The simulation is performed using Matlab/Simulink. The obtained results show that the filtering performances are well enhanced.